Design on orientation of one-dimensional ZnO/P(VDF-HFP) nanocomposites for significant enhanced electromechanical conversion. (1st March 2021) - Wang, Yalong; Xu, Meiyu; Zhang, Fengyuan; Wang, Yao; Zhang, Lingyu; Zhang, Qiang; Deng, Yuan
Abstract: Flexible piezoelectric generators (PEGs) are receiving considerable attention due to the increasing demands on lightweight and sustainable power supply for wearable electronics. Combing piezoelectric nanofillers with polymers have been extensively investigated as a promising strategy. Here, piezotronic ZnO nanorods are introduced into poly (vinylidene fluoride-hexafluoropropylene) [P(VDF-HFP)] considering that piezoelectric functions of both components can be united for high performance PEGs. ZnO/P(VDF-HFP) nanocomposites were designed with fillers distribution controlled via different processing, and the relationship between the filler orientation and the crystallization behaviors, dielectric and electromechanical conversion performances with respect to filler content were studied. The microcapacitor model and percolation theory were employed to understand the dielectric anisotropy in oriented nanocomposites, and furthermore, finite element analyses were utilized to reveal the distribution of local electric field. Finally, a maximum output voltage 11.8 V has been achieved in oriented ZnO/P(VDF-HFP) film, which is 2.3 times and 7.9 times the value of random nanocomposites (5.1 V) and pure P(VDF-HFP) film (1.5 V), respectively. With the piezoelectric responses obtained from piezoelectric force microscopy, significant enhancement in electromechanical conversion performance has been thoroughly discussed. The results thus demonstrate a promising strategy towards high-performance flexible piezoelectric generator. Graphical abstract: Image 1